Morphological Variables Associated With Ruptured Middle Cerebral Artery Aneurysms. Issue 1 (July 2019) - Zhang, Jian; Can, Anil; Mukundan, Srinivasan; Steigner, Michael; Castro, Victor M; Dligach, Dmitriy; Finan, Sean; Yu, Sheng; Gainer, Vivian; Shadick, Nancy A; Savova, Guergana; Murphy, Shawn; et al.
Abstract : BACKGROUND: : Geometric factors of intracranial aneurysms and surrounding vasculature could affect the risk of aneurysm rupture. However, large‐scale assessments of morphological parameters correlated with intracranial aneurysm rupture in a location‐specific manner are scarce. OBJECTIVE: : To investigate the morphological characteristics associated with ruptured middle cerebral artery (MCA) aneurysms. METHODS: : Five hundred sixty‐one patients with 638 MCA aneurysms diagnosed between 1990 and 2016 who had available computed tomography angiography (CTA) were included in this study. CTAs were evaluated using the Vitrea Advanced Visualization software for 3‐dimensional (3D) reconstruction. Morphological parameters examined in each model included aneurysm projection, wall irregularity, presence of a daughter dome, presence of hypoplastic or aplastic A1 arteries and hypoplastic or fetal posterior communicating arteries (PCoA), aneurysm height and width, neck diameter, bottleneck factor, aspect and size ratio, height/width ratio, and diameters and angles of surrounding parent and daughter vessels. Univariable and multivariable statistical analyses were performed to determine the association of morphological characteristics with rupture of MCA aneurysms. Logistic regression was used to build a predictive MCA score. RESULTS: : Greater bottleneck and size ratio, and irregular, multilobed, temporally projecting MCA aneurysms are associated with higher rupture risk, whereas higher M1/M2 ratio, larger width, and the presence of an ipsilateral or bilateral hypoplastic PCoA were inversely associated with rupture. The MCA score had good predictive capacity with area under the receiver operating curve = 0.88. CONCLUSION: : These practical morphological parameters specific to MCA aneurysms are easy to assess when examining 3D reconstructions of unruptured aneurysms and could aid in risk evaluation in these patients.